The Influence of Financial Literacy and Lifestyle on Hedonic Consumptive Behavior among Students at STIMIK Kreatindo Manokwari - Joice Pangulimang (Economics and Digital Business Review, 2025)
The purpose of this study was to determine the influence of financial literacy and lifestyle on the hedonic consumer behavior of STIMIK Kreatindo Manokwari students. The research sample consisted of 100 respondents, and the data analysis technique used multiple linear regression. The results of this study are as follows: 1) Financial literacy has a positive and significant effect on the hedonic consumer behavior of STIMIK Kreatindo Manokwari students. 2) Lifestyle has a positive and significant effect on the hedonic consumer behavior of STIMIK Kreatindo Manokwari students. 3) Financial literacy and lifestyle simultaneously have a positive and significant effect on the hedonic consumer behavior of STIMIK Kreatindo Manokwari students. Financial literacy and lifestyle are important factors that influence the hedonic consumer behavior of students, so efforts are needed to increase understanding of wise financial management and lifestyle control so that students can manage their finances more rationally and responsibly.